Efficacy of Bioenergetic Health Index to Predict Delirium After Major Abdominal Surgery in Elderly Patients: A Protocol for a Prospective Observational Cohort Study - Zhao, Yi; Liu, Juan; Ou, Mengchan; Hao, Xuechao (Frontiers in Medicine, 2022)
Introduction: Postoperative delirium (POD) commonly occurs after surgery and adversely threatens patients’ life quality, in particular the elderly. Mitochondria play a key role in the process of POD, which include inflammatory on the brain caused by surgeries and aging related neurodegeneration. As BHI (Bioenergetic Health Index) can be calculated from blood cells that represents a patient’s composite mitochondrial status. We hypothesize that the BHI of monocytes isolated from an individual’s peripheral blood can predict POD after major noncardiac surgery in elderly patients. Methods and analysis: This will be a prospective, single-site, single-blinded, randomized observational clinical trial. A total of 124 patients over 65 years old who will undergo major abdominal surgery lasting > 3 h will be enrolled. Preoperative and postoperative delirium will be determined using the Confusion Assessment Method. If patients are unable to speak in the ICU after surgery, the Confusion Assessment Method for the Intensive Care Unit will be utilized. All patients will undergo venous blood sampling before and 1 day after surgery (2 tubes, 5 mL/tube). Then, monocytes will be isolated and BHI will be measured. After discharge, patients will be followed-up by telephone for up to 30 days. The severity of complications will be categorized as: mild; moderate; severe; or fatal using a Clavien-Dindo classification. Discussion: This will be the first trial to investigate whether perioperative mitochondrial function of monocytes isolated from an individual’s blood can predict POD. By exploring new and more effective methods to predict POD, we hope to identify high risk patients before surgery and develop perioperative treatment strategies for them. Also, this study will advance the use of clinical investigations of mitochondrial functions during surgery. Trial registration number: Chinese Clinical Trial Registry, ChiCTR2100047554.